Extent of Serosal Changes Predicts Peritoneal Recurrence and Poor Prognosis After Curative Surgery for Gastric Cancer. Issue 42 (October 2015) - Kang, Yue; Li, Shenglong; Ge, Qinghong; Liu, Xinran; Yang, Zhenyu; Xue, Yingwei; Wang, Fujing
Abstract : Abstract: To investigate whether the width of gastric serosal lesions in advanced gastric cancer patients have a predictive value for peritoneal recurrence and the 5-year survival rate. A total of 1109 patients with advanced noncardia primary gastric adenocarcinoma, who underwent curative gastrectomy between January 1997 and December 2007, were included. Data about tumor size, longitudinal tumor location, resection type, serum albumin concentration, lymphatic/venous invasion, lymph node metastasis status, lesion size, histological and Borrmann type of tumor, as well as the recurrence rate and width of the gastric serosal lesions were collected and analyzed. The peritoneal recurrence rate in patients with gastric serosal lesions ≤3 cm was lower than in patients with gastric serosal lesions >3 cm. Multivariate analyses of the 5-year survival rate variables for all patients revealed significant correlations with serum albumin concentrations (HR 1.382, P = 0.002, 95% CI 1.123–1.701), width of serosa changes (HR 1.377, P = 0.020, 95% CI 1.053–1.802), depth of invasion (HR 1.529, P < 0.001, 95% CI 1.288–1.814), and lymph node metastasis (HR 1.551, P < 0.001, 95% CI 1.420–1.694), whereas for recurrent patients only serum albumin concentrations (HR 2.000, P < 0.001, 95% CI 1.425–2.805), width of serosa changes (HR 1.867, P = 0.002, 95% CI 1.248–2.793), and lymph node metastasis (HR 1.521, P < 0.001, 95% CI 1.249–1.852) correlated with the 5-year survival rate. Gastric serosal lesions >3 cm may indicate a high risk for peritoneal recurrence and serve as additional indicators for preventive postoperative adjuvant chemotherapies in patients with advanced gastric cancer.